ANALISA DAYA SAING PERUSAHAAN DITINJAU DARI ASSESMEN TEKNOLOGI - Ramadhani, Yuliastuti (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
Company X is a printing company such as making leaflets, banners, billboards and others. There is a competitors in the region makes the company must continue to increase its productivity in accordance with the development of existing technology in order to have a high level of competitiveness. The existence of competitors in the region makes the company must continue to increase its productivity in accordance with the development of existing technology in order to have a high level of competitiveness.The purpose of this study is to determine the strengths, weaknesses, opportunities, threats (SWOT) and determine performasi companies through content technology assessment (Technoware, Humanware, Infoware, and Orgaware) or THIO.The results showed that the SWOT method internal factors force score the highest points are the location of manufacturing sites is strategically located on the roadsite, the weakness factors is on the highest score of machinery because most existing engines are still using old technology, and opportunity analysis on external factors highest score is the level of technological progress, as well as a threat the highest score is the emergence of new competitors. While THIO obtained from the technological content of each component as follows: Technoware = 0633, Humanware = 0699, Infoware = 0439, Orgaware = 0498. In comparison has been measured also in similar companies in the company Y (as benchmarking) has a value of each component Technoware = 0.801; Humanware = 0.79; Infoware = 0.64; Orgaware = 0.78,.